The use of cognitive clinical interviews to explore learning from video game play - Holbert, Nathan; Russ, Rosemary S.; Davis, Pryce (2015)
As research about the learning that results when children play video games becomes more popular, questions arise about what methodological and analytical tools are most appropriate to access and document this learning. Thus far, researchers have mostly adopted pre/post assessments, ethnography, and learning analytics. In this paper we (re)introduce cognitive clinical interviews as a methodology particularly suited to answering many of the most pressing questions about games and learning. To that end we describe four challenges of studying learning in video games with pre-post assessments that we claim can be addressed by the addition of clinical interviews. We then consider how clinical interviews can help to explain and describe patterns detected from ethnographic observations and detailed game play logs.